Production of Rice in Water Deficient Regions - Subhashini S, Amar Shankar (International Journal of Modern Agriculture, 2021)
In Asia, rice production must increase in order to feed continuously increasing population. Although the water deficit for rice in Asia continues to be fully assessed, evidence suggests that a decline in water quality and water availability is putting the irrigated rice system at risk of sustainability. One of the main reason behind rain-fed rice high yields is Drought. There is a need to find various ways to grow rice with little available water in order to provide food security and meet hunger demand of world. The paper explores a systematic approach which involves genetics, breeding and integrally controlled capital, to growing rice yields and reducing water necessities for the production of rice. The various irrigation methods intended to save water, like cultivation of saturated soil as well as alternative wetting - drying can minimize unproductive water discharges while continuously growing water productivity. Additional modern methods are being studied to increase water efficiency without losing returns. In order to increase yield per unit of water, incorporate the C4 photosynthetic route in rice, use molecular biotechnologies to boost the resistance of droughts, and grow "aerobic rice" in non-flooded soil to achieve a healthy and safety yield.